Hubungan Perubahan Fisik dengan Tingkat Kecemasan Pasien Kemoterapi - Abusalam, Sulastri; Nuraina Sudirman, Andi; Syamsuddin, Fadly; Qomaria Usu, Siti (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Chemotherapy is one of the main treatment methods for cancer patients; however, it may cause various side effects in the form of physical changes that can affect patients’ psychological conditions. Physical changes such as nausea, vomiting, decreased appetite, hair loss, fatigue, weight loss, and changes in body appearance may become stressors that trigger anxiety in patients undergoing chemotherapy. This study aimed to analyze the relationship between physical changes and anxiety levels among patients undergoing chemotherapy in the Chemotherapy Unit of RSUD dr. Hasri Ainun Habibie, Gorontalo Province. This study used a quantitative correlational method with a cross-sectional approach. The sample consisted of 63 respondents selected using purposive sampling based on inclusion and exclusion criteria. Data were collected using a physical changes questionnaire and the Hamilton Anxiety Rating Scale (HARS) to measure anxiety levels. Data were analyzed using the Chi-Square test. The results showed that most respondents experienced severe physical changes, namely 27 respondents (42.9%), followed by moderate physical changes in 20 respondents (31.8%), and mild physical changes in 16 respondents (25.4%). The anxiety level of respondents was mostly in the moderate anxiety category, namely 30 respondents (47.7%), followed by mild anxiety in 20 respondents (31.8%), and severe anxiety in 13 respondents (20.7%). The Chi-Square test obtained a p-value of 0.0001, indicating a significant relationship between physical changes and anxiety levels among patients undergoing chemotherapy. The more severe the physical changes experienced by patients, the higher the anxiety level that may be felt during chemotherapy.